Islam Moderat dan Tradisi Keagamaan di Indonesia: Sinergi Ulama, Tarekat, dan Organisasi Islam - Eva Arianti (Jurnal Global Futuristik, 2025)
The spread of Islam in Indonesia took place through peaceful cultural and spiritual adaptation rather than through political domination. This process was deeply influenced by the role of ulama, tarekat (Sufi orders), and Islamic organizations that contributed significantly to the formation of Indonesia’s religious identity. This study aims to analyze how these three elements interact in shaping and maintaining Islamic traditions while promoting a moderate and inclusive understanding of Islam. The research uses a qualitative descriptive method with a library research approach by analyzing academic journals, books, and historical records related to Islamic education, spirituality, and institutional development. The results show that the collaboration among ulama, tarekat, and Islamic organizations forms a strong and synergistic relationship that strengthens Indonesia’s Islamic identity. Ulama act as moral and spiritual guides, tarekat serve as centers of inner purification and religious practice, while Islamic organizations institutionalize these values through education, preaching, and social empowerment. Together, they succeed in preserving Islamic traditions that are contextual, tolerant, and relevant to the dynamics of modern Indonesian society.